Die Klagenfurter "Landschaftsschule" als geistig-kulturelles Zentrum des Kärntner Protestantismus - Drobesch, Werner (Slavia Centralis, 2020)
Protestantism was not only present in the confessional and political field, but also in culture and spiritual life. An important role in the education system played the so-called provincial school as a half-university educational institution. The one in Klagenfurt was established with the help of the state between the years 1544 and 1551. In 1579, its school regulations were adapted to school regulations of provincial schools in Graz and Ljubljana, which resulted in the standardization of inner-Austrian educational space.